Shrimp pmo-miR-750 regulates the expression of sarcoplasmic calcium-binding protein facilitating virus infection in Penaeus monodon - Kanoksinwuttipong N. (2023)
MicroRNAs (miRNAs) regulate gene expression post-transcriptionally and play crucial roles in antiviral responses. Penaeus monodon miR-750 (pmo-miR-750) was found to be strongly up-regulated in the late phase of white spot syndrome virus (WSSV) infection, but its function remains uncharacterized. Herein, the targets that were translationally down-regulated in the shrimp stomach following a pmo-miR-750 mimic injection were identified using two-dimensional gel electrophoresis. Sarcoplasmic calcium-binding protein (Scp) and actin1 (Act1) were revealed to be down-regulated protein spots. The genuine binding of pmo-miR-750 mimic to Scp but not Act1 mRNA was validated in vitro. In addition, a negative correlation between the Scp transcript and pmo-miR-750 expression level in WSSV-infected P. monodon stomach implies that pmo-miR-750 regulates Scp expression in vivo. When injected into WSSV-infected shrimp, the pmo-miR-750 mimic suppressed Scp expression but significantly increased the WSSV copy number. Consistent with the miRNA mimic-mediated Scp suppression, the loss of function assay of Scp in WSSV-challenged shrimp by RNA interference revealed a decreased survival rate with a dramatic increase in viral copy number. Besides that, apoptosis was activated in the hemocytes of the Scp knockdown shrimp upon WSSV infection. Collectively, our findings reveal that up-regulated pmo-miR-750 suppresses Scp expression at both the transcript and protein levels in the late stage of WSSV infection, which contributes to modulating apoptosis and eventually enabling viral propagation.